Vermiculita como substrato para o teste de germinação de sementes de barbatimão - Martins, Cibele Chalita; Machado, Carla Gomes; Caldas, Isliana Griebler Ribeiro [UNESP]; Vieira, Israel Gomes (My University, 2011)
The objective of this research was to evaluate the use of vermiculite as a substrate for the germination test of 'barbatimão' seeds and to establish what would be the best granulometry and the best moisture intensity to germinate 'barbatimão' seeds. Four replications of 50 seeds were previously scarified with H 2SO 4 for 60 minutes. Afterwards, the following germination substrates were evaluated: paper rolls moistened with water equivalent to 2.5 times the weight of the dry paper (control); micron, super thin, thin and average sized vermiculite moistened with 0.5, 1.0, 1.5 and 2.0 times the weight of the dry paper. The germination temperature was 30°C. The percentage of normal seedlings was obtained seven days after sowing (first count) and, then, weekly (up to 28 days). Average time and relative distribution of germination were calculated. It was concluded that the germination of 'barbatimão' seeds can be carried out with either fine vermiculite moistened with water equivalent to 2.0 times the weight of the dry paper or average sized substrate moistened with water equivalent to 0.5 to 2.0 times the weight of dry paper. These treatments resulted in higher and faster germination (21 days), similarly to the paper roll method.
Vermiculite as substrate for germination of 'barbatimão' seeds
Keywords: Forest species; Moistening; Seedlings; Speed of germination